Factors influencing the process of learning mathematics among visually impaired and blind people. (January 2019) - Spinczyk, Dominik; Maćkowski, Michał; Kempa, Wojciech; Rojewska, Katarzyna
Abstract: Effective instruction and comprehension of mathematics are important for achieving academic and professional success but are especially difficult for visually impaired individuals because of the inherent difficulty in managing structural information included in math formulae. An evaluation of an alternative for computer-aided math instruction and comprehension among visually impaired students was developed, and the evaluation included seven detailed categories of factors: behavioral, emotional, cognitive, social, distracting, motivational, and modeling factors. Then, the proposed method was used to compare the alternative teaching method, including problem decomposition and vector knowledge, to the classical teaching method with a teacher. The assessment of the impact of the developed approach on improving the process of teaching mathematics in a group of blind and visually impaired students was carried out by the completion of a questionnaire prepared by a psychologist. The alternative teaching method achieved significantly better results in six of the seven proposed assessment categories. These experiments extend the knowledge base on the limitations and challenges associated with teaching and learning mathematics among blind people. Graphical abstract: Highlights: Effective instruction and comprehension of mathematics among blind people are significant and difficult issues. Factor categories for evaluating computer-aided math teaching and learning among visually impaired students were developed. The proposed evaluation method was used to compare classical and alternative teaching methods. The alternative method achieved significantly better results than the classical method in 6 of the 7 proposed categories. The conducted experiments extend the knowledge base on the effective teaching and learning of math among blind people.